Metabolism of Paeoniae Radix Rubra and its 14 constituents in mice - Zhang, Jing; Lv, Yang; Zhang, Jing; Shi, Wen-Jin; Guo, Xu-Yan; Xu, Jing-Jing; Wang, Peng-Pu; Chen, Xue-Tai; Xiang, Lin-Han; Xu, Feng; Wang, Xuan; Cai, Shao-Qing (Frontiers in Pharmacology, 2022)
Objective: Paeoniae Radix Rubra (PRR) is a commonly used traditional Chinese medicine with the effects of clearing away heat, cooling the blood, and relieving blood stasis. To (1) elucidate the metabolites and metabolic pathways of PRR and its 14 main constituents in mice and (2) reveal the possible origins of the known effective forms of PRR and their isomers, the metabolism of PRR in mice was systematically studied for the first time. Methods: PRR and its 14 constituents were administered to mice by gavage once a day for seven consecutive days, respectively. All urine and feces were collected during the seven days of dosing, and blood was collected at one hour after the last dose. Metabolites were detected and identified using high performance liquid chromatography with diode array detector and combined with electrospray ionization ion trap time-of-flight multistage mass spectrometry (HPLC-DAD-ESI-IT-TOF-MSn). Results: In total, 23, 16, 24, 17, 18, 30, 27, 17, 22, 17, 33, 3, 8, 24, and 31 metabolites of paeoniflorin, albiflorin, oxypaeoniflorin, benzoylpaeoniflorin, hydroxybenzoylpaeoniflorin, benzoyloxypaeoniflorin, galloylpaeoniflorin, lactiflorin, epicatechin gallate, catechin gallate, catechin, ellagic acid, 3,3'-di-O-methylellagic acid, methylgallate, and PRR were respectively identified in mice; after eliminating identical metabolites, a total of 195 metabolites remained, including 8, 11, 25, 17, 18, 30, 27, 17, 21, 17, 1, 2, 8, 20, and 20 newly identified metabolites, respectively. The metabolic reactions of PRR and its 14 main constituents in mice were primarily methylation, hydrogenation, hydrolysis, glucuronidation, and sulfation. Conclusions: We elucidated the metabolites and metabolic pathways of PRR and its 14 constituents (e.g., paeoniflorin, catechin, ellagic acid, and gallic acid) in mice and revealed the possible origins of the 10 known effective forms of PRR and their isomers. The findings are of great significance to studying the mechanism of action and quality control of PRR.